Production and Preservation of Marian Plum (Bouea Macrophylla) Nectar - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Marian plum (Bouea macrophylla) belongs to the cashew family (Anacardiaceae). The ripe fruit is yellow-orange, mango-like in character, roundish, and juicy with a sour to sweet taste according to the variety, and has a faint turpentine smell. The endosperm is white and pinkish purple, and has a bitter and astringent taste. Ripe fruits are consumed fresh, but sometimes they are made of whole or pieces of fruit in sugar syrup. It has a lot of vitamins and nutrients that’s good for health. In order to enhance its added value, this study focused on production and preservation of marian plum nectar. The effect of pH, sugar supplementation, temperature and time of pasteurization to sensory score of marian plum nectar; changes of total soluble solid, acidity and microbial load in marian plum nectar during storage were examined. Results showed that marian plum nectar had the best quality by adjusting at pH 4.2, sugar supplementation 6%, 95oC in 2.5 minutes, storage at 4 ± 2 ºC in glass bottle.Keywords: Bouea macrophylla, Supplementation, Pasteurization, Storage, Nectar, Acidity